'Coronavirus kindness' phenomenon: Trends of social flow of creativity during the first 27 days of social distancing in the COVID-19 pandemic in the United Kingdom. (1st June 2022) - Baracsi, Zita
This study elaborates on the contradictory position of socially supportive haptic arts and crafts in the light of recent social distancing requirements, in order to gain insight into the roles of the socially engaged field in the COVID-19 afflicted world. The contrast between the practices of extreme social distancing and intensive social engagement is astonishing, yet both of these practices became driving forces of daily life during the pandemic. This study is also concerned with the representation of socially supportive visual arts and crafts during the first 27 days of lockdown in the United Kingdom. By collecting mass media data of socially engaged grassroots events during the observed period and analysing them in context of social flow and personal needs fulfilment, which are viewed with an understanding of their non-hierarchical nature, it raises questions for further discussions on motivations of contributing to 'coronavirus kindness' and future possibilities for the socially engaged arts and crafts field.